2007
DOI: 10.1097/01.ccm.0000262386.32287.29
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-derived S100A12 in acute lung injury and respiratory distress syndrome

Abstract: S100A12 and its receptor RAGE are found at high concentrations in pulmonary tissue and bronchoalveolar lavage fluid in acute lung injury. S100A12 expression may reflect neutrophil activation during lung inflammation and contribute to pulmonary inflammation and endothelial activation via binding to RAGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
119
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 36 publications
8
119
1
Order By: Relevance
“…In blacks, there was a heightened neutrophil response to dental plaque accumulation; neutrophil hyperactivity has been shown to play a role in endothelial injury (Lentsch and Ward, 2000) and subsequent tissue damage in several disease processes (Di Filippo et al, 2007;Wittkowski et al, 2007). It was also suggested that long-term, low-grade infectious challenges may be of greater systemic importance than isolated, clinically obvious events (Roberts, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In blacks, there was a heightened neutrophil response to dental plaque accumulation; neutrophil hyperactivity has been shown to play a role in endothelial injury (Lentsch and Ward, 2000) and subsequent tissue damage in several disease processes (Di Filippo et al, 2007;Wittkowski et al, 2007). It was also suggested that long-term, low-grade infectious challenges may be of greater systemic importance than isolated, clinically obvious events (Roberts, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Morbini et al observed increased RAGE expression in patients with interstitial and postobstructive pneumonia [32]; this report left unanswered whether patients with bacterial pneumonia were included in the analysis. Notably, two other studies showed that constitutively present RAGE was not upregulated during pulmonary infl ammation associated with ALI or acute respiratory distress syndrome (ARDS): First, rats with ALI induced by intratracheally administered LPS displayed no change in the distribution of RAGEexpressing cells [29]; and second, patients with ARDS did not have increased pulmonary expression of RAGE [26].…”
Section: Rage Expression During Pneumoniamentioning
confidence: 99%
“…Furthermore, S100A12 -also known as EN-RAGE (extracellular newly identifi ed ligand of RAGE) or myeloid-related protein (MRP)-6 -is found in monocytes and lymphocytes and provokes pro-infl ammatory responses in endothelial cells [26]. Although many RAGE ligands are promiscuous with regard to receptor use, S100A12 has only been shown to bind to RAGE.…”
Section: S100a12mentioning
confidence: 99%
See 2 more Smart Citations